1996
DOI: 10.1080/13557858.1996.9961770
|View full text |Cite
|
Sign up to set email alerts
|

Suicide patterns and trends in people of Indian subcontinent and Caribbean origin in England and Wales

Abstract: This study confirms previous findings of high suicide rates in young Asian women. A new finding is the raised suicide rate in young Caribbeans. High suicide risks among young people from some ethnic minority communities are significant in the context of both the Health of the Nation strategy and recent governmental concern about the need to tackle health variations in the UK. Such deaths are indicative of larger numbers of young ethnic minority adults at risk of mental distress and self harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 21 publications
5
64
0
Order By: Relevance
“…Limited published research is available concerning the psychological health of Indian immigrant women in the United States. However, several studies examined mental health among Indian immigrant women in the United Kingdom, and found that the suicide rate of Indian immigrant women was higher than that of their male counterparts and of the indigenous populations of their adopted countries (Patel and Gaw 1996;Raleigh 1996). Patel and Gaw reported that family conflict was a common precipitating factor, as did Hicks and Bhugra (2003).…”
Section: Psychological Health Of Asian Indian Women In Americamentioning
confidence: 96%
“…Limited published research is available concerning the psychological health of Indian immigrant women in the United States. However, several studies examined mental health among Indian immigrant women in the United Kingdom, and found that the suicide rate of Indian immigrant women was higher than that of their male counterparts and of the indigenous populations of their adopted countries (Patel and Gaw 1996;Raleigh 1996). Patel and Gaw reported that family conflict was a common precipitating factor, as did Hicks and Bhugra (2003).…”
Section: Psychological Health Of Asian Indian Women In Americamentioning
confidence: 96%
“…Several large-scale studies have been carried out (Hunt et al, 2003;Soni Raleigh, 1996) plus a number of small-scale local studies from the 1980s and 1990s. Generalisations are difficult owing to variation in definition of South Asian, the reliability of coroners' records, methodological problems and geographical variation.…”
Section: (V) Suicidementioning
confidence: 99%
“…1,2 Rates of suicide 3,4 and self-harm [5][6][7] may be lower in BME groups than White groups overall, but this finding may obscure differences in age-and gender-specific groups. Also, rates of suicide and self-harm within ethnic minority groups may fluctuate according to area, with a decline in relative risk of suicide and self-harm where there is a larger density of minority populations.…”
mentioning
confidence: 99%